2011
DOI: 10.1160/th11-04-0254
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation and activated protein C resistance in the absence of factor V Leiden correlates with the risk of recurrent venous thromboembolism in women aged 18–65 years

Abstract: Identification of patients at high risk of recurrence after a first event of venous thromboembolism (VTE) remains difficult. Resistance to activated protein C (APC) is a known risk factor for VTE, but data on the risk of recurrence is controversial. We wanted to investigate whether APC resistance in the absence of factor V Leiden, determined with global coagulation test such as the thrombin generation assay, could be used as a marker for increased risk of recurrent VTE among women 18-65 years old after a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…The association of inflammation biomarkers with diagnosis, severity, and poor prognosis of cerebrovascular events has already been reported, especially in patients with CVST [ 15 , [20] , [21] , [22] , [23] , [24] , [25] ]. Recently, a multicenter prospective observational study was conducted in Portugal: the Pathophysiology of Venous Infarction – Prediction of Infarction and Recanalization in CVT (PRIORITy-CVT) study, including 62 patients, demonstrated that biomarkers associated with inflammation predicted poor prognosis in cerebral vein thrombosis (CVT) [ 15 ]. In this study, patients had more unfavorable outcomes than the FPCCVT cohort (21% vs 3% of deaths, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of inflammation biomarkers with diagnosis, severity, and poor prognosis of cerebrovascular events has already been reported, especially in patients with CVST [ 15 , [20] , [21] , [22] , [23] , [24] , [25] ]. Recently, a multicenter prospective observational study was conducted in Portugal: the Pathophysiology of Venous Infarction – Prediction of Infarction and Recanalization in CVT (PRIORITy-CVT) study, including 62 patients, demonstrated that biomarkers associated with inflammation predicted poor prognosis in cerebral vein thrombosis (CVT) [ 15 ]. In this study, patients had more unfavorable outcomes than the FPCCVT cohort (21% vs 3% of deaths, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…No study has yet evaluated the association of D-dimer with CVST clinical manifestations. Besides, thrombin generation (TG) has been proposed as a global assay to evidence hypocoagulable [ 10 , 11 ] and hypercoagulable states [ [12] , [13] , [14] ]: increased TG is an independent predictor of recurrent venous thrombosis [ 15 ]. Inflammation biomarkers, such as fibrinogen and high-sensitivity C-reactive protein (hs-CRP), have been recently described as possible predictors of poor prognosis in CVST [ 16 ].…”
Section: Introductionmentioning
confidence: 99%